Focal localization of inflammatory cytokines and neurotrophins in a tongue chronic injury model. (March 2019) - Neupane, Sanjiv; Jung, Hyun-Guek; Sohn, Wern-Joo; Yamamoto, Hitoshi; Kim, Ji-Youn; Byun, Jin-Seok; Lee, Youngkyun; Bae, Yong Chul; Choi, Jae-Kap; Kim, Jae-Young; Jung, Jae-Kwang
Highlights: Chronic tongue injury model using silk suture was first established and described. Our model revealed region specific localization of MPO, MMP2, TNFα, NGF and TRPV1. Prolonged injury may contribute altered neuronal function on antero-ventral tongue. Our model is useful to unravel pathological mechanism of neuropathic pain like BMS. Abstract: Objectives: Chronic injury in tongue causes the variety of reactions in the oral cavity, frequently leading to its functional and structural disintegrity including inflammation and sensory dysfunction, but its detailed profiles were not elucidated yet. One of the chronically injured tongue such as tongue piercing, as a pathological aspect, is currently popular among younger people but may be associated with severe side effects, leading to pathophysiological complications. However, the pathophysiological aspects and related cellular and molecular mechanisms underlying tongue injury are not clearly understood. Design: In this study, we designed an experimental model system using C57BL/6 male mice that mimics a chronically injured situation by penetrating the middle part of tongue with silk suture. After 5 and 10 days mice were sacrificed and tongues were collected and processed for histological evaluation and immunohistochemistry. Results: We found that the anterior tongue showed localization of neuro-inflammatory signaling molecules such as myeloperoxidase (MPO), matrix metalloproteinase 2 (MMP2), tumor necrosis factor-α (TNF-α), nerve growth factor, and transient receptor potential cation channel subfamily V member 1 (TRPV1) without any apparent inflammation in temporal manner. In addition, the signal for AM1-43, an activity-dependent nerve terminal probe, decreased within the fungiform papillae on the anterior tongue after injury. Conclusions: These results implied that the distinct localizations of inflammatory cytokines and neurotrophin would contribute altered sensory function in anterior tongue following the chronic injury. Our study indicates the possible pathophysiologic mechanism underlying neuro-inflammation following chronically injury of tongue. In addition, it could be cautiously postulated that mechanical injury should be avoided to prevent chronic pain disorders from being triggered.